Automatic metamodel-driven service component model generation - Ding, Xinyang (Nanyang Technological University, 2025)
Model-Driven Development (MDD) represents a paradigm shift in software engineering, offering numerous benefits that can lead to more efficient, reliable, and maintainable software systems. It shifts the focus from traditional coding to creating and evolving high-level abstract models, which are then transformed into executable code. With growing software complexity, MDD is expected to become a key approach in shaping future software engineering practices.